Nigeria - China Trade Relations: Oil Resource in Focus, 1990s - 2020 - Oladimeji, Talibu; Samuel, Abejide Taye; Ovuete, Aghalino Samuel (Hasanuddin Journal of International Affairs, 2025)
This paper examines Nigeria foreign policy and business ethics, particularly its bilateral relations with China between 1990s and 2020. It further explores China’s interest in the oil sector. It argues that China’s quest for oil security has attracted it to many African countries. Although, Nigeria and China diplomatic relations began in February 1971, its relations were not sealed until 1999, when the military surrendered power to a democratically elected government. It explains that a number of bilateral agreements between the two countries endured China’s readiness to finance infrastructural development in Nigeria. This paper further evaluates the economic and trade links between the two countries and its impact on Nigeria economic performance. With the use of appropriate statistical data, integration of primary and secondary sources, the paper addresses the security challenges to China’s quest to penetrate Nigeria’s oil sector in the Niger Delta. It concludes that since China is the second largest importer of crude oil in the world, there is urgent need for Nigerian government to re-direct its foreign policy in order to ensure smooth relations with China. This would to a large extent enhance the acceleration of socio-economic development of the oil producing communities in Niger Delta and the country at large.